What is the expression in factored form?
x2 + 14x + 48
A. (x + 6)(x - 8)
B. (x + 8)(x - 6)
C. (x - 8)(x - 6)
D. (x + 6)(x + 8)

Question

Asked 1/22/2013 5:08:22 PM

Updated 6/3/2014 11:18:48 PM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/3/2014 11:05:52 PM]

s

OxTornado007|Points 6599|

Booknerd_lizzy|Points 350|

jeifunk|Points 8461|

OxTornado007|Points 6599|

eturker|Points 2852|

eturker|Points 2852|

OxTornado007|Points 6599|

OxTornado007|Points 6599|

ephraimzRN|Points 2278|

OxTornado007|Points 6599|

Comforse49|Points 60|

OxTornado007|Points 6599|

businesslady|Points 1113|

rugmaker|Points 2525|

philliphughes|Points 130|

Question

Asked 1/22/2013 5:08:22 PM

Updated 6/3/2014 11:18:48 PM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/3/2014 11:05:52 PM]

Rating

3

(3 + i) - (2 - 2i)

= 3 + i - 2 + 2i

= 1 + 3i

= 3 + i - 2 + 2i

= 1 + 3i

Added 6/3/2014 11:05:48 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/3/2014 11:09:50 PM]

3

x^2 + 18x + 81 = 25

x^2 + 18x + 81 - 25 = 0

x^2 + 18x + 56 = 0

(x + 4)(x + 14) = 0

x = -4 or x = -14

x^2 + 18x + 81 - 25 = 0

x^2 + 18x + 56 = 0

(x + 4)(x + 14) = 0

x = -4 or x = -14

Added 6/3/2014 11:07:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/3/2014 11:09:27 PM]

3

-x^3 + 5x^2 - 11x + 55 = 0

-x^2(x - 5) - 11(x - 5) = 0

(x - 5)(-x^2 - 11) = 0

x - 5 = 0 or -x^2 - 11 = 0

x = 5 or x = ± (sqrt 11)i

-x^2(x - 5) - 11(x - 5) = 0

(x - 5)(-x^2 - 11) = 0

x - 5 = 0 or -x^2 - 11 = 0

x = 5 or x = ± (sqrt 11)i

Added 6/3/2014 11:11:12 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 12:58:23 PM]

3

x^3 - 2x^2 + 10x + 136 = 0

(x + 4)(x^2 - 6x + 34) = 0

x + 4 = 0 or x^2 - 6x + 34 = 0

When x + 4 = 0, x = -4

When x^2 - 6x + 34 = 0

x = [6 ± sqrt (-100)]/2 = (6 ± 10i)/2 = 3 ± 5i

The solution is {-4, 3 + 5i, 3 - 5i)

(x + 4)(x^2 - 6x + 34) = 0

x + 4 = 0 or x^2 - 6x + 34 = 0

When x + 4 = 0, x = -4

When x^2 - 6x + 34 = 0

x = [6 ± sqrt (-100)]/2 = (6 ± 10i)/2 = 3 ± 5i

The solution is {-4, 3 + 5i, 3 - 5i)

Added 6/3/2014 11:18:48 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 12:58:51 PM]

31,870,193

questions answered

There are no comments.